O serviço social na efetivação dos direitos à saúde dos usuários com doença renal crônica (DRC) - Silva, Viviane Alves da (Universidade Federal do Tocantins, 2021)
Therefore, the general objective of the present work is to understand the importance of Social Service in the realization of the health rights of users with renal disease chronic renal disease, which stresses the chronic renal person a great erosion and a series of limitations that involve the biological, psychological and social, because in this context, the practical intervention of the social worker is present and necessary. This research is grounded in Marx's critical dialectical method. For the accomplishment of this work the bibliographic research was used as methodological procedure. The work focuses on the historical context of the Health Policy, advances and setbacks, entering into the Unified Health System and we also deal with Social Work and its historical context and finally we highlight Social Service in the realization of the rights to Health of people with DRC, as has been the struggle for the rights of these users, understanding the current neoliberal conjuncture, and health is going through a moment of total lack of investment, dismantling of public policies and precariousness. Therefore, Social Work is very important for the improvement of the life conditions of the user with CKD, since their process of illness, the demands of the treatment and the changes in their daily life, involve procedures related to social factors that are not performed by any other health professional, but by the social worker. From this perspective, research has shown that Social Work has an important impact on the complexity of treatment. He is an important professional in the joint service with health teams, users with CKD and family, providing and disseminating information and actions that contribute to the improvement of services and the realization of social rights.